1980
DOI: 10.1002/aic.690260106
|View full text |Cite
|
Sign up to set email alerts
|

Moving‐bed solids flow in an inclined pipe leading into a fluidized bed: Part II. The solids flow properties

Abstract: The purpose of part 11 of this paper is to theoretically analyze and experimentally examine moving-bed solids flow in an inclined pipe connecting a fluidized bed and a solids storage vessel. The macroscopic momentum balance equation is simplified and applied to the present system. A friction factor correlation is developed. Based on the flow curves constructed, we found that the power law model is suitable for describing moving-bed solids Bow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1985
1985
1989
1989

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The investigation of the rheological properties of a solid-gas suspension in a cocurrent flow made by Chen, Walavender and Fan [10] was based on the analysis of pseudo-shear diagrams. The authors found that the systems under consideration had pseudoplastic properties and that the deviation from Newtonian behaviour depended on the slip velocity of solid particles and the geometrical arrangement of the distributor of solid particles at the entrance to the equipment.…”
Section: Introductionmentioning
confidence: 99%
“…The investigation of the rheological properties of a solid-gas suspension in a cocurrent flow made by Chen, Walavender and Fan [10] was based on the analysis of pseudo-shear diagrams. The authors found that the systems under consideration had pseudoplastic properties and that the deviation from Newtonian behaviour depended on the slip velocity of solid particles and the geometrical arrangement of the distributor of solid particles at the entrance to the equipment.…”
Section: Introductionmentioning
confidence: 99%
“…The first assumption is important for calculating the turbulent characteristics #t and L, because apart from theoretical considerations, experimental work by Chen et al [12] and Lodes et al [13] have confirmed the pseudoplastic character of the flow of a suspension of solid particles in a gas.…”
Section: Theorymentioning
confidence: 94%